AB1085-HPR Audit of Nurse-Led DGH Rheumatology Advice Line. (15th July 2016) - Bellerby, T.; Stevens, D.; Arnold, T.; Kerton, L.; Ortiz, G.; Price, E.; Collins, D.; Ahmed, A.; Carty, S.; Williamson, L.
Abstract : Background: We introduced a nurse led Rheumatology Advice Line in 2004 to offer telephone advice to patients with inflammatory arthritis (1). Since then there has been a year-on-year increase in the number and complexity of calls, putting unsustainable demand on service and staff. A service review in April 2014 demonstrated one third of calls were inappropriate, including calls about the Home delivery service, appointment times and general practice related problems. We therefore changed the recorded message with the expectation that the helpline be used for telephone consultations concerning: medication side effects and effectiveness; flares of arthritis; possible complications of biologics and DMARDs; results of blood and X-Ray tests to avoid outpatient appointments. We audited the use of the Advice Line. Methods: We documented the number of calls to the Advice Line from 2004–2014. The recorded message for the Advice Line was altered in May 2014. We audited the calls in April 2014 and compared with data from calls between May and December 2015. All calls were documented and categorised as: Patient calls leading to clinic appointment; Patient calls with advice give related to medication or inflammatory arthritis; GP or district nurse calls with advice given; Home delivery related; Inappropriate calls (including non rheumatological conditions, appointment time related, in-house calls). We also documented whether letters were generated and made a judgement about whether Consultant or GP consultation had been avoided Results: The total annual number of calls increased from 438 in 2004; 2752 in 2006; 3074 in 2008; 2817 in 2010; 3857 in 2012; 3210 in 2014. After the recorded message was changed, the number of inappropriate calls fell from 97/311 (31.2%) in April 2014 to 8/258 (3.1%) from April to December 2015. However the number of appropriate calls rose from 131/311 (42.1%) in April 2014 to 194/258 (75.2%). The complexity and time needed to deal with calls has also increased. Conclusions: The Rheumatology Nurse Practitioner led Advice Line provides a valuable clinical service as an adjunct to face to face consultation. This audit suggests a saving over 100 face-to-face consultations per month. Changing the Advice Line message led to a fall in the number of inappropriate calls but the number and complexity of calls continues to increase. This will need to be reflected in future service evaluation. References: RA Hughes. Telephone Helplines in Rheumatology Rheumatology, Vol 42. 197–199 (2003) Disclosure of Interest: None declared